Kesenjangan Kualitas Sekolah: Tantangan Pemerataan Pendidikan Dasar di Pesisiran Jawa dan Implikasinya di ranah Keberagaman islam - Rohmah, Alifa Rizqi Kaila Ainur; Azwa Qonitatun; Sahra Naura Luwistiana; Zulfasa Kaila Yuniasih (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2026)
Abstract: This study aims to deeply analyze the gap in basic education in Weleri District, Kendal Regency, Central Java Province, Indonesia, specifically Weleri Village, correcting the initial focus that was directed at the UIN campus environment. Using a qualitative approach with a case study design, data were collected through unstructured interviews, participant observation, and document analysis, then analyzed using the Miles and Huberman interactive model with source triangulation techniques to ensure data validity involving eight key informants. The most important findings reveal that the educational gap in Kendal is a manifestation of significant multidimensional structural injustice, encompassing spatial disparities, educational attainment, and the distribution of human resources. Spatially, there is a concentration of quality schools in the center of Weleri District, while coastal areas experience limited access due to the